Toxic thyroid adenoma with hypercalcemia mimicking an intra-thyroidal parathyroid adenoma - Venkata Subramanian Krishnaraju; Ritesh Upadhyay; Ashwani Sood; Anish Bhattacharya; Bhagwant Mittal (Asia Oceania Journal of Nuclear Medicine and Biology, 2022)
Hypercalcemia is a clinical condition characterized by elevated circulating serum calcium levels either due to raised parathyroid hormone in hyperparathyroidism or due to secondary causes of hypercalcemia without elevated parathyroid hormone levels. However, hyperthyroidism may occasionally present with incidentally detected hypercalcemia. We present a case of a 53-year-old woman with a previous history of an underlying thyroid disorder, now presented with features of hypercalcemia and mildly elevated parathyroid hormone levels. Her ultrasonography of the neck was suggestive of an intra-thyroidal parathyroid adenoma and it was localized as a tracer avid lesion within the thyroid gland on dual-phase 99mTc-sestamibi planar scintigraphy with single photon emission computed tomography/ computed tomography (SPECT/CT). However, a subsequent thyroid profile followed by 99mTc- pertechnetate thyroid scintigraphy showed a hot nodule in the thyroid gland which changed the diagnosis to a toxic thyroid adenoma. She was treated with radioactive iodine ablation and thyrotoxicosis resolved and the serum calcium levels normalized on her follow-up.